Online Compulsive Buying and Brand Addiction in Indonesia: The Importance of Using Fear of Missing Out and Social Commerce Interactivity - Ardyan, Elia; Sanapang, Gracela Marisa (Journal The Winners, 2023)
The research aimed to investigate the impact of fear of missing out and interactivity on online compulsive buying and brand addiction, drawing upon the theoretical framework of compensating the internet use method. The data were obtained through an online questionnaire, which was satisfactorily filled out by 133 participants. The participants were individuals who had engaged in online compulsive buying behavior and exhibited addiction to purchasing specific brands. The statistical data analysis involved utilizing structural equation modeling with partial least squares (SEM-PLS). The findings indicate that the presence of fear of missing out and interactivity have the potential to enhance consumers’ propensity to engage in online compulsive buying and develop brand addiction. Individuals who exhibit a proclivity for engaging in obsessive online purchasing behavior might have been incentivized to develop brand addiction. The researchcontributes to the existing literature on the theory of compensating internet use. It proposes that individuals may be motivated to participate in online activities to alleviate negative feelings from challenging situations.